When God came to Town - Urban Development and Religious Practices in early medieval Odense, Denmark - Haase, Kirstine; Manøe Bjerregaard, Mikael (Danish Journal of Archaeology, 2022)
This article presents a contextual approach to studying the role of the urban environment in introducing Christianity to Denmark between 900 and 1250. We consider sensory experience and apply the concept of lived religion to the highly varied and sometimes limited archaeological material from St Alban’s church in Odense, its cemetery, and the surrounding settlement, to show that the urban environment played an active role in integrating Christianity into everyday life. The church and king used the urban environment to stage their authority. The message of Christianity was propagated through religious practices, such as celebrating Saint Cnut with spectacular processions, and dress accessories with religious motifs. These practices facilitated the transformation from an elite-oriented missionary religion promoted by the king and the elite to a widely accepted religion integrated into the everyday lives of Odense’s inhabitants.